LEARNING MODEL DEVELOPMENT BASED ON ENVIRONMENTAL EDUCATION USING WETLAND AT ISLAMIC ELEMENTARY SCHOOLS IN BANJARMASIN - khairunnisa .; Salamah . (EDUSAINS, 2018)
PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS PENDIDIKAN LINGKUNGAN DENGAN LAHAN BASAH PADA MADRASAH IBTIDAIYAH DI KOTA BANJARMASIN   Abstract This research is aimed to know how the environmental based learning by introducing wetland at Islamic elementary schools in Banjarmasin have been going recently (teachers’ understanding, design, process, and learning evaluation),and how are the learning model which is based on environmental education on wetland can be developed and implemented at Islamic elementary schools in Banjarmasin.This research is a developmental research with Research and Development (R&D) approach through preliminary research, small scale testing model development, and wide scale testing model validation. The research is conducted at MI Darun Nasihin, MI Sulamut Taufiq, and MI Nurul Islam.The data is collected through documentation, questionnaires, interview, and observation. The data is analyzed descriptive-qualitatively through data reduction, data display, and verification. After wide scale testing on the model which was developed and tried out using learning instrument adapted with the materials about ecosystem balance, the materials were then taught to the six graders of Islamic elementary school through the following implementation steps: orientation, relating, exploration, finding problems, group investigation, work result discussion, clarification, and resolution. The model is proved to be able to be developed at Islamic elementary schools in Banjarmasin, viewed from the students learning evaluation with the percentage in very good category. Students behavior also shows positive influence which means the learning has been able to stimulate students’ positive behaviors such as caring, being open-minded, being appreciative to what people are saying, and being responsible.The model development is also supported by good response from students and teachers towards students’ workbook and teaching learning process.  Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana pembelajaran berbasis lingkungan dengan memperkenalkan lahan basah di sekolah dasar Islam di Banjarmasin telah berjalan baru-baru ini (pemahaman, desain, proses, dan evaluasi pembelajaran guru), dan bagaimana model pembelajaran yang didasarkan pada pendidikan lingkungan di lahan basah dapat dikembangkan dan diimplementasikan di sekolah dasar Islam di Banjarmasin. Penelitian ini merupakan penelitian pengembangan dengan pendekatan Research and Development (R & D) melalui penelitian pendahuluan, pengembangan model pengujian skala kecil, dan validasi model pengujian skala luas. Penelitian dilakukan di MI Darun Nasihin, MI Sulamut Taufiq, dan MI Nurul Islam. Data dikumpulkan melalui dokumentasi, angket, wawancara, dan observasi. Data dianalisis secara deskriptif-kualitatif melalui reduksi data, tampilan data, dan verifikasi. Setelah pengujian skala luas pada model yang dikembangkan dan diujicobakan menggunakan instrumen pembelajaran yang disesuaikan dengan materi tentang keseimbangan ekosistem, materi kemudian diajarkan kepada enam siswa sekolah dasar Islam melalui langkah-langkah implementasi berikut: orientasi, berhubungan, eksplorasi, penemuan masalah, investigasi kelompok, diskusi hasil kerja, klarifikasi, dan resolusi. Model ini terbukti dapat dikembangkan di sekolah dasar Islam di Banjarmasin, dilihat dari evaluasi pembelajaran siswa dengan persentase dalam kategori sangat baik. Perilaku siswa juga menunjukkan pengaruh positif yang berarti pembelajaran telah mampu merangsang perilaku positif siswa seperti kepedulian, berpikiran terbuka, menghargai apa yang dikatakan orang, dan bertanggung jawab. Pengembangan model juga didukung oleh respon yang baik dari siswa dan guru terhadap buku kerja siswa dan proses pembelajaran.   Permalink/DOI: http://dx.doi.org/10.15408/es.v10i1.7217